Pendampingan Penyusunan Laporan Keuangan BUMDesa Bersama di Kabupaten Karanganyar - Nuryadi, Muhammad Hendri; Kurniawan, Itok Dwi; Septiningsih, Ismawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Village-Owned Enterprises (BUMDesa) are business entities owned and managed by villages together with village communities with the aim of increasing independence, togetherness, and mutual cooperation. However, BUMDes still faces various technical and operational obstacles, especially in the preparation of good and correct financial statements. In fact, financial statements are official documents that contain information about the financial position of BUMDes in a certain period to provide an accurate and transparent picture related to BUMDes finances to stakeholders. This research aims to overcome this problem through assistance carried out by the Karanganyar Regency Dispermades with the PKM-HGR UNS PUSLITDESBANGDA Service Team. The method used is Participatory Action Research (PAR) which involves the active participation of all BUMDes elements during the mentoring process. This assistance aims to provide solutions to existing problems and create more effective, transparent, and sustainable management of BUMDes. After the implementation of this assistance, it is hoped that it can improve the professionalism of financial management, managerial skills, transparency and accountability, access to external financial resources, community empowerment, and the continuity and growth of BUMDes.